1985
DOI: 10.1029/jb090ib04p03105
|View full text |Cite
|
Sign up to set email alerts
|

Compression‐induced microcrack growth in brittle solids: Axial splitting and shear failure

Abstract: Micromechanisms of rock failure (axial splitting and shear failure) are examined in light of simple mathematical models motivated by microscopic observations. The elasticity boundary value problem associated with cracks growing from the tips of a model flaw is solved. It is shown that under axial compression, tension cracks nucleate at the tips of the preexisting model flaw, grow with increasing compression, and become parallel to the direction of the maximum far‐field compression. When a lateral compression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
309
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 863 publications
(328 citation statements)
references
References 47 publications
14
309
0
5
Order By: Relevance
“…This frictional influence of adjacent microcolumns on the failure of rock was therefore considered by Renshaw and Schulson [95] and found a twofold lesser failure stress compared to Horii and Nemat-Nasser [93] Ashby and Hallam [97] models. However, crack growth in all of these studies has been arrested at similar crack lengths when compressive forces normal to the crack growth direction present.…”
Section: Refs Governing Equation Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This frictional influence of adjacent microcolumns on the failure of rock was therefore considered by Renshaw and Schulson [95] and found a twofold lesser failure stress compared to Horii and Nemat-Nasser [93] Ashby and Hallam [97] models. However, crack growth in all of these studies has been arrested at similar crack lengths when compressive forces normal to the crack growth direction present.…”
Section: Refs Governing Equation Remarksmentioning
confidence: 99%
“…Nemat-Nasser and Horii [93] conducted uniaxial compression on plates of a brittle material to investigate the behaviour of a preexisting planar crack set when it at different orientations to the major principal stress (σ1). The frictional sliding (τ) between the faces was found to produce wing cracks at crack tips, which deviate sharply from the sliding plane and continue to grow steadily towards the axis of major principal stress with increasing compressive strength (see Figure 13).…”
Section: Microcrack Based Sliding Crack Modelsmentioning
confidence: 99%
“…The vertical failure zones outside the jog, which are observed in the present numerical results, are especially similar to splitting cracks from a slip interface in the simplified model of [Ewy and Cook 1990]; see Figure 7(d). Wing fractures originating from a preexisting fracture were also observed in many experiments [Horii and Nemat-Nasser 1985;Shen et al 1995;Dyskin et al 1999;Saimoto et al 2003]. Using a displacement discontinuous method, Shen and Stephansson found that a stiff contact condition (high normal fracture stiffness and high shear fracture stiffness) produces straight wing fractures similar to the present vertical failure zones, while a noncontact condition (zero normal fracture stiffness and zero shear fracture stiffness) leads to curved wing fractures analogous to the present wing failure zones.…”
Section: 2mentioning
confidence: 94%
“…1). Symmetric cracks initiated at the crown and base of the hole propagate along the axis of the specimen in the direction of the applied compression (Horii and Nemat-Nasser 1985). The test is stable when the compression required to grow the cracks increases with crack length.…”
Section: Introductionmentioning
confidence: 98%